Between religion and empire: Sarah Selwyn’s Aotearoa/New Zealand, Eton and Lichfield, England, c.1840s-1900 - MacDonald, Charlotte (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2008)
AbstractTaking the life of Sarah Selwyn (1809-1907), wife of the first Anglican bishop to New Zealand, the article plots the dynamics of geographic movement and varying communities of connection through which the mid-19thC imperial world was constituted. Negotiating empire and religion, mission and church, high church and evangelical, European and indigenous Maori and Melanesian, Sarah’s life illuminates the intricate networks underpinning – and at times undermining – colonial governance and religious authority. Sarah embarked for New Zealand in late 1841 at a high point of English mission and humanitarian idealism, arriving into a hierarchical and substantially Christianised majority Maori society. By the time she departed, in 1868, the colonial church and society, now European-dominated, had largely taken a position of support for a settler-led government taking up arms against “rebellious” Maori in a battle for sovereignty. In later life Sarah Selwyn became a reluctant narrator of her earlier “colonial” life while witnessing the emergence of a more secular empire from the close of Lichfield cathedral. The personal networks of empire are traced within wider metropolitan and colonial communities, the shifting ground from the idealistic 1840s to the more punitive later 19thC. The discussion traces the larger contexts through which a life was marked by the shifting ambiguities of what it was to be Christian in the colonial world: an agent of empire at the same time as a fierce critic of imperial policy, an upper class high church believer in the midst of evangelical missionaries, someone for whom life in New Zealand was both a profound disjuncture and a defining narrative.